On a criterion of NP-completeness - Bulitko, V. V.; Bulitko, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider the problem of construction of criteria of completeness of sets with respect to polynomially bounded reducibilities. We present a nonstandard description of sets from the class NP, a brief proof of an analog of the well-known Cook theorem, and a criterion of NP-completeness.